Endocrine Disruptors: an occupational risk for healthcare professionals - Birelo de Almeida, Chayene (2025)
Endocrine disruptors (EDCs) are exogenous chemical substances present in the environment and in commonly used objects that cause harm to human health. This study aimed to conduct a bibliographic survey on DECs that can pose occupational risks to healthcare professionals. The SciELO, BVS and PubMed databases were searched, crossing the descriptors in Portuguese Disruptor Endócrino, Saúde Pública, Esterilização e Produtos Químicos, and in English Endocrine Disruptor, Public Health, Sterilization and Endocrine-Disrupting Chemicals, selecting articles from the period 2018 to 2023. A total of 12,483 articles were found, most of which described the harmful aspects to the environment. After further cross-referencing between the descriptors, 64 articles were selected among reviews and meta-analyses, none of which directly addressed the exposure of healthcare professionals. The results indicate several substances posing significant risks, such as bisphenol found in laboratory plastic consumables, and ethylene oxide, used in hospital sterilization, which can lead to reproductive, neurological and metabolic dysfunctions. It is concluded that specific workplace guidelines and preventive measures to minimize the impact of DECs are urgently needed. Studies are needed to quantitatively assess exposure and long-term effects, promoting safer work environments.